INTEGRASI SELF-DETERMINATION THEORY DAN AGILE LEADERSHIP UNTUK TRANSFORMASI MOTIVASI KERJA DAN PRESTASI KARYAWAN: STUDI KUALITATIF DI INDUSTRI TEKNOLOGI INDONESIA - Inge Gunawan; Ingrid Panjaitan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study explores the integration of Self-Determination Theory (SDT) and Agile Leadership in enhancing work motivation and performance in the Indonesian technology industry. Using a qualitative approach, this study explores employee perceptions of SDT-based training supported by agile leadership practices. Data were collected through in-depth interviews with 18 employees and six leaders from three technology companies in Jakarta, as well as an analysis of company training documents. The findings indicate that training that supports autonomy, competence, and social connectedness, combined with adaptive agile leadership, significantly improves intrinsic motivation and performance. The novelty of this study lies in the integration of SDT and Agile Leadership in the Indonesian context, providing theoretical and practical contributions to human resource management in the technology industry. Practical implications include recommendations for designing training that focuses on psychological needs and developing leadership responsive to industry dynamics.